2017
DOI: 10.1080/14737167.2017.1358617
|View full text |Cite
|
Sign up to set email alerts
|

Estimate of the cost of multiple sclerosis in Spain by literature review

Abstract: Multiple Sclerosis (MS) is a progressive disease leading to increasing disability and costs. A literature review was carried out to identify MS costs and to estimate its economic burden in Spain. Areas Covered: The public electronic databases PubMed, ScienceDirect and IBECS were consulted and a manual review of communications presented at related congresses was carried out. A total of 225 references were obtained, of which 43 were finally included in the study. Expert Commentary: Three major cost groups were i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 52 publications
0
27
1
Order By: Relevance
“…Fatigue and cognitive complaints were found in 92 and 64% of participants, respectively. Fatigue and cognitive disturbances are much more common than mobility problems in people who are working [8, 19]. MS-related productivity loss due to presenteeism was three times that of absenteeism in a study with 740 MS employees conducted in Australia [4].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Fatigue and cognitive complaints were found in 92 and 64% of participants, respectively. Fatigue and cognitive disturbances are much more common than mobility problems in people who are working [8, 19]. MS-related productivity loss due to presenteeism was three times that of absenteeism in a study with 740 MS employees conducted in Australia [4].…”
Section: Discussionmentioning
confidence: 99%
“…In some European countries, MS caregivers provide 150 h a month of care to pwMS, the equivalent of full-time employment [1]. The mean annual cost per patient in Spain was €30,050 [8]. Sicras et al found that only 30% of MS people were employed or self-employed [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to a cross-sectional Spanish study [6], 92% and 64% of patients with MS analyzed experienced fatigue and cognitive problems, respectively, with a mean utility (quality of life as perceived by the patient) of 0.772 and costs per patient per year (from the societal perspective) ranging between 20,600 € with a score in the Expanded Disability Status Scale (EDSS) of 0 to 3 and 68,700 € with an EDSS score of 7 to 9. In Spain, the total annual cost of MS has been estimated at 1,4 billion euros (40% direct healthcare cost, 30% direct non-healthcare cost and 30% indirect cost) [7].…”
Section: Introductionmentioning
confidence: 99%
“…Mental and neurological disorders also have a substantial economic impact in Spain (equivalent to almost 8% of the country’s GDP) with a mean yearly per-patient cost of €30,050 for MS patients [ 14 , 15 ]. However, information about the use of healthcare resources and associated costs among patients with MS in Spain is limited.…”
Section: Introductionmentioning
confidence: 99%